Identification of cultivars of foxtail Mollet (Setaria italica (L.) Beauv.) from morphological and biochemical traits of their seed - Pallares, I. N. (2004)
The objective of this research was to characterise three cultivars of Setaria italica (L.) Beauv. "Foxtail millet": Ñandú INTA, Carapé INTA and Yaguané INTA by means of their seeds. The methodologies applied were: description of seed size, shape and weight, chemical changes to the phenol test, ferrous sulphate test and fluorescence tests, and polyacrylamide gel electrophoresis of proteins. ANOVA and comparison means test (Tukey, p<0.05) were performed. This study revealed that, with the exception of the fluorescence test, Yaguané, Carapé and Ñandú cultivars could be identified by using the set of methodologies considered.